2017
DOI: 10.1002/mawe.201600776
|View full text |Cite
|
Sign up to set email alerts
|

Weld strength in solid–state recycling of aluminum chips

Abstract: In solid‐state recycling, chip morphology related parameters such as size fraction, surface topography and geometry are important factors in resulting final bond strength. Analyzing deformation parameters together with chip morphology can provide an insight of which factors are very crucial to mechanical performance of the recycled chips. This work investigates the effect of chip morphology and in particular chip roughness and surface area on the weld strength of direct recycled aluminum chips. The influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…A trend towards resource-efficient manufacturing can be observed in recent years driven by public concerns for environmental protection and resource conservation, but also as a result of the prospective stricter policies on climate change [1][2][3]. Non-ferrous metal recycling has a number of benefits, the most outstanding being the potential to reduce the extraction of virgin ores considerably, thus preserv-ing those non-renewable resources [4,5]. In terms of energy consumption, relying on the types of metals and the forms of scraps, recycling can save as much as a factor of 10 or 20 [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A trend towards resource-efficient manufacturing can be observed in recent years driven by public concerns for environmental protection and resource conservation, but also as a result of the prospective stricter policies on climate change [1][2][3]. Non-ferrous metal recycling has a number of benefits, the most outstanding being the potential to reduce the extraction of virgin ores considerably, thus preserv-ing those non-renewable resources [4,5]. In terms of energy consumption, relying on the types of metals and the forms of scraps, recycling can save as much as a factor of 10 or 20 [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of energy consumption, relying on the types of metals and the forms of scraps, recycling can save as much as a factor of 10 or 20 [6,7]. Today an increasing amount of the aluminium going into producing new aluminium alloy products is coming from recycled products [8,9]. Casting aluminumsilicon alloy has been widely used in industry and transportation for high strength, low density, excellent casting properties and many other advantages [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improved solid state recycling process is a typical environmentally benign manufacturing process for aluminium alloys. Solid-state recycling, which involves direct recycling of metal scrap into bulk material using severe plastic deformation, has emerged as an alternative to conventional remelting and recycling techniques [ 1 , 2 , 3 ]. More waste generation was observed than from conventional recycling (melting), and it was also reported that primary aluminium is depleted and other resources should be utilized as alternative materials.…”
Section: Introductionmentioning
confidence: 99%
“…Although metal recycling has many advantages, it has not been spared from environmental dispute. In recent years, many attempts have been made to create environmentally-friendly recycling technologies that are adaptable, reliable, energy saving, free from harmful substances, and reduce production waste and harmful emissions [ 4 , 5 ]. Direct conversion methods of recycling aluminum have many benefits, including cost and energy savings, and environmental protection by reducing the hazardous gas emissions compared to traditional recycling methods [ 1 ].…”
Section: Introductionmentioning
confidence: 99%